When Founders Lead: Independent Directors, Institutional Ownership, and Firm Value - Teddy Jurnali; Sheila Septiany; Jolin Floren Elvinis; Iskandar Itan; Budi Chandra (Jurnal Dinamika Akuntansi dan Bisnis, 2026)
This paper aims to examine the relationship between founder on board of directors and firm value, considering the moderating roles of independent directors and institutional ownership. The study sample includes 2,141 observations of companies listed on the Indonesia Stock Exchange for the 2018–2022 period, and was analyzed using panel regression. The results in this paper show that the founder on the board has a negative and significant effect on firm value, while institutional ownership strengthens the relationship, and independent directors have no effect. These findings emphasize the importance of institutional investors as a governance mechanism capable of controlling potential agency conflicts due to founder dominance. This study contributes to the corporate governance literature in emerging markets. It provides practical implications for regulators, investors, and family firms in optimizing the role of founders in creating firm value.